Pterocarpus santalinus (Red Sanders) an Endemic, Endangered Tree of India: Current Status, Improvement and the Future - Arunkumar, AN; Joshi, G (Journal of Tropical Forestry and Environment, 2014)
Pterocarpus santalinus (Family – Fabaceae) popularly known as Red Sanders is an endemic species confined to Southern parts of Eastern Ghats of India specially in Andhra Pradesh. Heartwood of Red Sanders has high demand in domestic as well as international market and the wavy grained wood is valued. Along with its extensive use in furniture, the red dye obtained from the wood is used as colouring agent for textile, medicine and food. The heartwood can accumulate various elements and rare earth elements like strontium cadmium, zinc, copper and uranium. The wood has different uses in traditional and folklore medicines and is used for the treatment of diabetes, prickly heat, skin diseases and for various other ailments. A number of studies have been carried out to anatomically and phenotypicaly screen wavy grain at seedling stage. Morphological variability and genetic diversity studies reveal that Red Sanders harbours enormous variability. Though, macro and micro propagation protocol have been developed, further refinement is required for mass propagation. Andhra Pradesh Forest Department has also initiated different activities under tree improvement programme. Considering the wood demand, restricted distribution, slow regeneration, illegal harvest, trade and habitat destruction, the species has been categorized as endangered by International Union for Conservation of Nature and has been listed in Convention on International Trade in Endangered Species of Wild Fauna and Flora and is also classified as a “reserved tree” under the Andhra Pradesh Preservation of Private Forest Rules, 1978. To revive the past glory of this valuable species, Government agencies, farmers, entrepreneurs and policy makers have to join hands for its protection, sustainable utilization and conservation.